Office Size of Big 4 Auditors and Client Restatements - Francis, Jere R.; Michas, Paul N.; Yu, Michael D. (Contemporary Accounting Research, 2013)
Francis and Yu (2009) and Choi, Kim, Kim, and Zang (2010) report evidence that Big 4 audits are of higher quality when the engagement office is of larger size. Specifically, client earnings quality is higher and auditors in larger offices are more likely to issue going‐concern audit reports. We extend this line of research to test if larger Big 4 offices have fewer client restatements. A client restatement provides more direct evidence of a low‐quality audit than earnings quality metrics or going‐concern reports, because a restatement indicates the client's auditor did not effectively enforce the correct application of GAAP at the time the original financial statements were issued. We analyze 2,557 firm‐year restatements in a sample of 23,190 financial statements originally issued by U.S. firms from 2003 to 2008. We find that Big 4 office size is associated with fewer client restatements after controlling for innate client characteristics that may affect restatements (client size, financial performance, industry membership, nonfinancial measures, off‐balance sheet activities, and market‐related measures), and a set of controls for other auditor factors such as fees and industry expertise. The study raises important questions about the ability of smaller offices to deliver high‐quality audits for SEC registrants.